Specific inhibition of NADPH oxidase 2 modifies chronic epilepsy - Prince Kumar Singh; Aseel Saadi; Yara Sheeni; Tawfeeq Shekh-Ahmad (Redox Biology, 2022)
Recent work by us and others has implicated NADPH oxidase (NOX) enzymes as main producers of reactive oxygen species (ROS) following a brain insult such as status epilepticus, contributing to neuronal damage and development of epilepsy. Although several NOX isoforms have been examined in the context of epilepsy, most attention has focused on NOX2. In this present study, we demonstrate the effect of gp91ds-tat, a specific competitive inhibitor of NOX2, in in vitro epileptiform activity model as well as in temporal lobe epilepsy (TLE) model in rats. We showed that in in vitro seizure model, gp91ds-tat modulated Ca2+ oscillation, prevented epileptiform activity-induced ROS generation, mitochondrial depolarization, and neuronal death. Administration of gp91ds-tat 1 h after kainic acid-induced status epilepticus significantly decreased the expression of NOX2, as well as the overall NOX activity in the cortex and the hippocampus. Finally, we showed that upon continuous intracerebroventricular administration to epileptic rats, gp91ds-tat significantly reduced the seizure frequency and the total number of seizures post-treatment compared to the scrambled peptide-treated animals.The results of the study suggest that NOX2 may have an important effect on modulation of epileptiform activity and has a critical role in mediating seizure-induced NOX activation, ROS generation and oxidative stress in the brain, and thus significantly contributes to development of epilepsy following a brain insult.